PENGARUH PANDEMI COVID-19 TERHADAP INTENSITAS PENGGUNAAN E-WALLET - Rachel Andriana; Arina Falabiba; Firnanda Permata Dilla; Muhammad Eka Marshanda Pramestyan; Dwi Yuli Rakhmawati (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The Covid-19 pandemic has forced some people's activities to switch from offline to online. These activities include work, school, including transaction activities. Transacting with e-wallet is an option during the pandemic because it can reduce direct contact The purpose of this research is to analyze and test the effect of the covid-19 pandemic on the intensity of e-wallet use. This analysis uses an independent variable, namely the covid-19 pandemic and the dependent variable, namely the intensity of e-wallet use. This type of research is quantitative research with data collection techniques through the distribution of surveys or questionnaires filled out by 100 samples. The analytical technique used in this research is simple linear regression with the help of SPSS 18 software. The results of this research indicate that the covid-19 pandemic positively affects the intensity of e-wallet use.